Optical implementation of a constant-time multicomparand bit-parallel magnitude-comparison algorithm using wavelength- and polarization-division multiplexing with application to parallel database processing - Detofsky, A; Choo, P Y; Louri, A (Optics letters, 1998)
We present a word- and bit-parallel magnitude-comparison architecture that permits multiple comparands to be compared with multiple relations in constant time. The proposed magnitude-comparison algorithm uses a novel polarization and wavelength-encoding scheme to achieve a fast, scalable realization. Distinctive features of the proposed architecture include (1) the use of a multiple-wavelength encoding scheme to increase processing parallelism and (2) multiple-comparand word- and bit-parallel comparison with an execution time that is independent of the data or word size.